Lexical Reiteration in EFL Students’ Academic Writing - Nurul Maghfirah Bobihoe; Zulkifli Tanipu; Fahria Malabar (Transbahasa, 2025)
This study examines the use of lexical reiteration in the academic writing of EFL (English as a Foreign Language) students at Gorontalo State University. Lexical reiteration, encompassing repetition, synonyms and near-synonyms, superordinates, and general words, is crucial for maintaining cohesion and coherence in texts. Using Halliday and Hasan’s (1976) cohesion theory, this research analyzes various academic texts produced by fifth-semester students. The findings reveal that repetition is the most frequently used type of reiteration, followed by synonyms and near-synonyms, general words, and superordinates. However, a major issue identified is the excessive reliance on repetition, resulting in monotonous writing. This problem stems from a limited academic vocabulary and inadequate knowledge of cohesive devices. As a result, students struggle to create well-structured and engaging academic texts. This study highlights the need for expanding vocabulary and improving students’ understanding of lexical cohesion to enhance their writing quality. By addressing these challenges, educators can help students develop more varied and effective academic writing skills. These findings contribute to discussions on improving EFL students’ writing proficiency, particularly in terms of lexical cohesion and coherence.